Coastal Vulnerability Assessment Using CVI in Kedung and Tahunan - Raihan Rahmat Darmawan; Tjaturahono Budi Sanjoto (Universitas Negeri Gorontalo, 2026)
Coastal areas are increasingly exposed to environmental pressures, such as erosion, shoreline change, and sea-level rise, which threaten the sustainability of coastal systems and human activities. This study aimed to assess coastal vulnerability in the Kedung and Tahunan subdistricts using the coastal vulnerability index (CVI). The analysis integrated physical and socioeconomic parameters, including shoreline change, geomorphology, wave conditions, sea-level rise, tidal range, coastal slope, land use, population density, sex ratio, age structure, and poverty rate. Data were obtained from field surveys, secondary sources, and Landsat 8 imagery and processed using geographic information systems (GIS) and the digital shoreline analysis system (DSAS). The results showed clear spatial variations in vulnerability at the village level. Panggung exhibited the highest CVI value (25.5), indicating high vulnerability, whereas Kedungmalang (6.81), Bulakbaru (5.11), Semat (6.14), and Telukawur (6.14) fell into the moderate category. Kalianyar (4.09), Surodadi (3.06), Tanggultlare (0.68), and Tegalsambi (3.07) showed lower vulnerability levels. These differences were influenced by the interaction between physical coastal conditions and socioeconomic characteristics, particularly population density, demographic structure, and poverty levels. The findings demonstrate that the CVI approach provides a comprehensive representation of coastal vulnerability and offers a useful basis for spatially informed coastal management and risk reduction strategies.